New trends and platforms for quantum technologies - Aguado, Ramón (Lecture notes in physics, 2024)
This book serves as a comprehensive introduction to quantum computing platforms, inspired by recent advancements in quantum technologies aimed at detecting and manipulating single quantum objects. Encompassing solid-state, atomic, and optical platforms, it delves into various aspects of quantum computing, including topological quantum computing. The content covers the fabrication, modeling, and numerical implementation of quantum circuits, such as Josephson junctions and qubits, along with hybrid nanostructures. Additionally, the book introduces quantum entanglement, a crucial concept for quantum communication and information processes. The well-compiled topics and concise presentation position the book as a primer for courses on quantum technologies